2015
DOI: 10.4103/0189-6725.151003
|View full text |Cite
|
Sign up to set email alerts
|

Repair of tracheo-oesophageal fistula secondary to button battery ingestion: A combined cervical and median sternotomy approach

Abstract: A three-year-old child developed a large tracheo-oesophageal fistula secondary to a button battery being lodged in the upper oesophagus for 36 hours. The diagnosis was confirmed with a contrast swallow. Operative access was gained through a combined right cervical incision and complete median sternotomy. Repair of the fistula required a segmental resection of both the trachea and oesophagus followed by primary anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…4,6 Not witnessed ingestions and nonspecific symptoms and signs often lead to misdiagnosis or late diagnosis. 7…”
mentioning
confidence: 99%
“…4,6 Not witnessed ingestions and nonspecific symptoms and signs often lead to misdiagnosis or late diagnosis. 7…”
mentioning
confidence: 99%
“…Non-intervention management should first be tried to manage tracheoesophageal fistulas acquired in children [26]. Gopal et al (2015) reported a case in which a three-year-old child developed a large tracheoesophageal fistula for 36 h due to the placement of a button battery. Surgical access was obtained through right cervical incision and median sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheoesophageal fistulas (TEF) may be complicated by the high incidence of comorbidities such as recurrent laryngeal nerve injury, tracheal stenosis, recurrent fistula, or even mortality. Studies of medical records of children with vocal cord paralysis and esophageal lithium battery ingestion have shown that it may cause serious complications such as esophageal perforation, mediastinal infection, tracheal fistula, vocal cord paralysis, and life-threatening bleeding [4][5][6]. In a study, a 16-month-old boy with lithium battery ingestion developed bilateral voice paralysis due to misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the identification of the nerve trunks is necessary and the anatomical distribution in the distal part of the esophagus is determinant for the results and to avoid post-operative morbidity (Miyano et al, 2015;Razumosky et al, 2015). Segmental resection of the esophagus (Gopal et al, 2015) is not a frequent operation but the surgical results depend on the location and extension of the damaged segment, and the possibility to save the nerve trunks and branches. Esophageal replacement (with colon) for the treatment of congenital or acquired atresia in children or adults, with or without fistula, and unavoidable sacrifice of vagus nerves is the most extended procedure with higher morbidity and mortality (Spitz, 2014;Ezemba, 2014;Fragoso et al, 2015;Ortiz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%